Ivermectin as a novel complementary malaria control tool to reduce incidence and prevalence: a modelling study. Issue 4 (April 2020) - Slater, Hannah C; Foy, Brian D; Kobylinski, Kevin; Chaccour, Carlos; Watson, Oliver J; Hellewell, Joel; Aljayyoussi, Ghaith; Bousema, Teun; Burrows, Jeremy; D'Alessandro, Umberto; Alout, Haoues; Ter Kuile, Feiko O; et al.
Summary: Background: Ivermectin is a potential new vector control tool to reduce malaria transmission. Mosquitoes feeding on a bloodmeal containing ivermectin have a reduced lifespan, meaning they are less likely to live long enough to complete sporogony and become infectious. We aimed to estimate the effect of ivermectin on malaria transmission in various scenarios of use. Methods: We validated an existing population-level mathematical model of the effect of ivermectin mass drug administration (MDA) on the mosquito population and malaria transmission against two datasets: clinical data from a cluster- randomised trial done in Burkina Faso in 2015 wherein ivermectin was given to individuals taller than 90 cm and entomological data from a study of mosquito outcomes after ivermectin MDA for onchocerciasis or lymphatic filariasis in Burkina Faso, Senegal, and Liberia between 2008 and 2013. We extended the existing model to include a range of complementary malaria interventions (seasonal malaria chemoprevention and MDA with dihydroartemisinin–piperaquine) and to incorporate new data on higher doses of ivermectin with a longer mosquitocidal effect. We consider two ivermectin regimens: a single dose of 400 μg/kg (1 × 400 μg/kg) and three consecutive daily doses of 300 μg/kg per day (3 × 300 μg/kg). We simulated the effect of these two doses in a range of usage scenarios in different transmission settings (highly seasonal, seasonal, and perennial). We report percentage reductions in clinical incidence and slide prevalence. Findings: We estimate that MDA with ivermectin will reduce prevalence and incidence and is most effective in areas with highly seasonal transmission. In a highly seasonal moderate transmission setting, three rounds of ivermectin only MDA at 3 × 300 μg/kg (rounds spaced 1 month apart) and 70% coverage is predicted to reduce clinical incidence by 71% and prevalence by 34%. We predict that adding ivermectin MDA to seasonal malaria chemoprevention in this setting would reduce clinical incidence by an additional 77% in children younger than 5 years compared with seasonal malaria chemoprevention alone; adding ivermectin MDA to MDA with dihydroartemisinin–piperaquine in this setting would reduce incidence by an additional 75% and prevalence by an additional 64% (all ages) compared with MDA with dihydroartemisinin–piperaquine alone. Interpretation: Our modelling predictions suggest that ivermectin could be a valuable addition to the malaria control toolbox, both in areas with persistently high transmission where existing interventions are insufficient and in areas approaching elimination to prevent resurgence. Funding: Imperial College Junior Research Fellowship.